2010
DOI: 10.1080/08946566.2011.534704
|View full text |Cite
|
Sign up to set email alerts
|

Elder Abuse: Factors Related to Perceptions of Severity and Likelihood of Reporting

Abstract: This study examined factors that affect assessments of abuse as depicted in scenarios in which a caregiving daughter abuses her elderly mother through over-medication. College students (N = 239) read scenarios that varied in terms of the past quality of the caregiver/elder relationship and whether or not the elder adult was depicted as suffering from dementia. The role of the participants' own family caregiving experiences also was explored. Results from a factorial ANOVA showed that individuals who perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Elder abuse is difficult to define and poorly understood because it is often a hidden offence and the nature of the abuse alters in different regions of the world [15] [16], while it can be described as "any knowing, intentional or negligent act by a caregiver or any other person that causes harm or a serious risk of harm to a vulnerable adult" [16]. Western countries classify elder abuse as either being physical, emotional, financial, sexual and neglectful.…”
Section: Elder Abuse Toward Individuals With Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…Elder abuse is difficult to define and poorly understood because it is often a hidden offence and the nature of the abuse alters in different regions of the world [15] [16], while it can be described as "any knowing, intentional or negligent act by a caregiver or any other person that causes harm or a serious risk of harm to a vulnerable adult" [16]. Western countries classify elder abuse as either being physical, emotional, financial, sexual and neglectful.…”
Section: Elder Abuse Toward Individuals With Dementiamentioning
confidence: 99%
“…Extreme physical forms of violence, such as stabbing older people with knives, burning or murdering were not reported in the study. In Southern Africa such incidents are more common, but poorly reported [15] due to beliefs that the odd behavior of PWD is synonymous with witchcraft practices [20]. Another common type of elder abuse reported by the UK National Elder Abuse Study is that of a financial nature.…”
Section: Elder Abuse Toward Individuals With Dementiamentioning
confidence: 99%
“…This increase in elder abuse has been recognized not only in Japan but also in other countries, with the associated problems classified into four groups, ie, neglect, emotional abuse, physical abuse, and financial exploitation 2. Physical abuse is defined as acts of violence that cause pain, injury impairment, or disease, and involves behaviors such as hitting, slapping, and kicking 2. Studies of senile dementia have reported that in some cases, the physical abuse can become so severe that it leads to the death of the patient 3.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main approaches recommended for reducing elderly consumer fraud victimization consists of social service, legal, and education programs, coordinated through state or local agencies, that provide crime prevention information and assistance (Fitzpatrick & Hamill, 2010; Reeves & Wysong, 2010). Such efforts remain largely unevaluated, and so their effectiveness remains unknown (Daly et al, 2011; Hafemeister, 2003; Johnson, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the greater potential risk of fraud victimization and to becoming an ever-larger proportion of the U.S. population, the elderly typically underreport victimization (Fitzpatrick & Hamill, 2010). Together with the substantial harms that arise from victimization, including the financial impacts and their adverse sequelae, such considerations have given rise to programs aimed at preventing and reducing elderly consumer fraud victimization.…”
Section: Introductionmentioning
confidence: 99%